2023
DOI: 10.1002/lno.12346
|View full text |Cite
|
Sign up to set email alerts
|

Size fractionated biogeochemical constituents across adjacent coastal systems informs approaches for integrating small catchment studies into regional models

Abstract: Observed and predicted hydrological changes in C‐rich boreal ecosystems have the ability to change the transport trajectory of biogeochemical constituents from the land to ecologically, economically, and culturally important coastal systems. Yet, most of our current understanding of biogeochemical fluxes and cycling across salinity gradients stem from observations of large and urbanized riverine systems, which overlooks the numerically abundant smaller systems. In this study, we conducted a baseline assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…Comparing δ 13 C org against source data from Khoo et al ( 2023) suggests surface sediment in and around each eelgrass meadow was a combination of terrestrial and marine derived sources, but predominantly marine derived (Figure 6a). This was supported by the C:N ratio, which also overlapped with the marine and terrestrial source C:N ratios reported in Khoo et al (2023), and in some cases even overlapped with the eelgrass C:N ratio (i.e., Swift Current) and the Redfield ratio for plankton (C:N of 6.6; Redfield, 1958) (Figure 6b). However, C org was predominantly supplied from marine sources other than the eelgrass themselves, given that δ 13 C org in the seagrass tissue (−11.64 ± 1.8‰) was overall ∼10‰ more enriched than the surface sediment (Figure 6a).…”
Section: Tablesupporting
confidence: 73%
See 2 more Smart Citations
“…Comparing δ 13 C org against source data from Khoo et al ( 2023) suggests surface sediment in and around each eelgrass meadow was a combination of terrestrial and marine derived sources, but predominantly marine derived (Figure 6a). This was supported by the C:N ratio, which also overlapped with the marine and terrestrial source C:N ratios reported in Khoo et al (2023), and in some cases even overlapped with the eelgrass C:N ratio (i.e., Swift Current) and the Redfield ratio for plankton (C:N of 6.6; Redfield, 1958) (Figure 6b). However, C org was predominantly supplied from marine sources other than the eelgrass themselves, given that δ 13 C org in the seagrass tissue (−11.64 ± 1.8‰) was overall ∼10‰ more enriched than the surface sediment (Figure 6a).…”
Section: Tablesupporting
confidence: 73%
“…Swift Current is located in the most developed region of the three sites, where there is a community <1 km from the meadow (population of 207; Statistics Canada, 2022), but on the opposite side of the inlet. Freshwater entering the system is carbon-rich, as it primarily originates from boreal forest draining catchments (Khoo et al, 2023). Eelgrass at the three sites is exposed predominantly to semidiurnal tides and estuarine circulation with lower salinity at low tide and higher salinities at high tide.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation